A Survey for Some Kinds of Livestock’s Ticks in Dhi-Qar and AL-Muthanna Governorates/Iraq - Mohammed. J. Falih, Abbas. K. Hamza, (Pakistan Journal of Medical & Health Sciences, 2022)
In this study, a survey was conducted to determine the types and the prevalence of ticks parasitizing livestock in south of Iraq, namely Dhi-Qar and AL-Muthanna governorates. The study continued for five months, from the beginning of October 2021 until the end of February 2022. During this period, samples were collected from sheep, cows, buffaloes and camels from different regions within the tow mentioned governorates. The results recorded the presence of six species of ticks infecting livestock, all of which belongs to the genus Hyalomma, where the type H.anatolicum had the highest infection prevalence, which was (32.87%). While the rest species recorded as the follows H.marginatum (20.17%), H.excavatum (18.99%), H.dromedarii (18.89%), H.scupense (8.00%), and H.truncatum (1.06%) as the latter recorded the lowest prevalence among the diagnosed species. The total infection rate was 59.65% (346 out of 580), and according to the governorate, The highest infection prevalence was in Dhi-Qar, which recorded about (61.75%), while AL-Muthanna recorded (57.08%), for animal type, the highest rate recorded in camels (77.14%), while buffalos recorded the lowest rate (47.85%), of the five months, October recorded the highest infection prevalence that was (77.5%), while January recorded the lowest infection prevalence that was (32.2%). Keywords: Livestoks Ticks, Dhi-Qar, AL-Muthanna